Comparison between S-ketamine and clonidine in caudal analgesia - Ribeiro, Onesimo D.; Abreu, Luiz Carlos de [UNESP]; Valenti, Vitor Engrácia [UNESP]; Cisternas, Jose Raul; Saletti, Deise; Lima, Carla J. B.; Silvestre, Diego N.; Godoy, Ivan R. B.; Mello, Luiz G. M.; Nascimento, Vania B.; Martins, Lourdes C. (Academic Journals, 2011)
We aimed to compare the analgesic efficacy of the caudal administration of a combination of preservative free S-ketamine or clonidine with bupivacaine in children. The study included 51 children aged between 3 and 8 years old and physical status between I and II according to: American Society of Anesthesiologist. They were randomly divided into three groups: Group B - bupivacaine 0.25%, 0.75 ml/kg without adrenaline; Group C - bupivacaine 0.25%, 0.75 ml/kg without adrenaline and clonidine 1 mu g/kg and; Group K - bupivacaine 0.25%, 0.75 ml/kg without adrenaline and S-ketamine 0.5 mg/kg without conservative. In this study, medication was not used before anesthesia. The evaluation of postoperative analgesia was accomplished through the pain scale of Ouch, the motor blockade assessed by modified Bromage scale and the level of sedation through the three-point scale. The combination of caudal S-ketamine and clonidine with bupivacaine prolonged the duration of postoperative analgesia (p < 0.05) compared to bupivacaine alone. Regarding hemodynamic parameters, bupivacaine associated with clonidine (C) and bupivacaine associated with S-ketamine (K) groups presented diastolic blood pressure changes in the postoperative period. Respiratory rate, regardless of group, showed significant differences over time (p < 0.05). The studied groups showed non significant changes in the degree of motor blockade and sedation score and we observed no clinical significant side effects. S-ketamine and clonidine associated with bupivacaine prolongs postoperative analgesia without clinically significant side effects.
Keywords: Pediatric assistants; anesthesia; analgesia; epidural; anesthesia; caudal; anesthetics